2021
DOI: 10.3389/fvets.2021.792647
|View full text |Cite
|
Sign up to set email alerts
|

Owner's Perception of Seizure Detection Devices in Idiopathic Epileptic Dogs

Abstract: Accurate knowledge of seizure frequency is key to optimising treatment. New methods for detecting epileptic seizures are currently investigated in humans, which rely on changes in biomarkers, also called seizure detection devices. Critical to device development, is understanding user needs and requirements. No information on this subject has been published in veterinary medicine. Many dog health collars are currently on the market, but none has proved to be a promising seizure detector. An online survey was cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The SDS can have several benefits in veterinary medicine. Numerous studies showed that the caregivers of epileptic dogs, particularly those who have less time to supervise the dog directly, experience stress and anxiety due to unpredictable seizures ( 2 , 4 , 6 ). Medical staff may have a similar experience because continuous monitoring is not always easy in some busy clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDS can have several benefits in veterinary medicine. Numerous studies showed that the caregivers of epileptic dogs, particularly those who have less time to supervise the dog directly, experience stress and anxiety due to unpredictable seizures ( 2 , 4 , 6 ). Medical staff may have a similar experience because continuous monitoring is not always easy in some busy clinics.…”
Section: Discussionmentioning
confidence: 99%
“…A seizure detection system (SDS) that can be used for continuous monitoring and the detection and notification of seizures can reduce burden among owners and veterinarians. Based on a recent study, the owners of dogs with epilepsy want to use a seizure detection device ( 6 ). Such a system can accurately identify seizure frequency, which is important for the medical/surgical treatment of epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there is only one non-EEG device tested in dogs, leaving many opportunities to further explore non-EEG seizure detection devices in veterinary medicine. User needs for dog owners appear similar to caregivers for people as for example they both value a high accuracy but would also accept a high false alarm rate ( 2 , 61 ). Although the information on study design and device properties in humans is extensive and could potentially be translated to animals, there are many more challenges faced during the design of such a study in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, seizure counts based on seizure diaries are often inaccurate and underestimated ( 351 , 352 ). Similar to the situation in human epilepsy, the unpredictability of seizures plays a major part in the management of canine epilepsy, and dog owners have a strong desire to know when a seizure occurs ( 353 ). Automated seizure detection by reliable seizure detection devices would be important to guide treatment decisions or monitor outcomes in clinical trials in both human and canine patients.…”
Section: Use Of Dogs As a Translational Model In Epilepsy Research An...mentioning
confidence: 99%